Racial Socialization in Two Cultures - Sugoto, Srisiuni; Yusof, Aminuddin Mohd (ANIMA Indonesian Psychological Journal, 2008)
The study of racial socialization is important because it expands the scope of past research on African American, Hispanic, or Asian people in the United States. The goal of this paper is to ex- amine the differences of parent racial socialization in Malaysia and Indonesia (especially in Sura- baya). The present study investigated whether the practice of four types of parental racial socializa- tion are reflected in a sample of 400 parents (Malay Malaysians, Chinese Malaysians, Javanese in Su- rabaya, and Chinese in Surabaya). Parent racial socialization was assessed using yes or no answers to questions related to socialization practice in a family. Results indicated that no differences between father’s and mother’s racial socialization of all subjects. Based on ethnicity, there were significant dif- ferences which Malay Malaysia parents have highest score emphasizing racial pride and promotion of mistrust for their children. Implication will be discussed. Studi sosialisasi rasial penting karena meluaskan liputan penelitian terhadap masyarakat Afrika Amerika, Hispanik, atau Asia di Amerika Serikat. Tujuan artikel ini adalah meneliti perbedaan sosialisasi rasial orang tua di Malaysia dan Indonesia (terutama di Surabaya). Studi ini menginvestigasi apakah praktik empat jenis sosialisasi rasial orang tua terefleksi dalam sampel sejumlah 400 orang tua (Melayu Malaysia, China Malaysia, Jawa Surabaya, dan China Surabaya). Sosialisasi rasial orang tua dinilai berdasarkan jawaban ya atau tidak terhadap pertanyaan terkait praktik sosialisasi dalam keluarga. Hasil menunjukkan tak adanya perbedaan antara sosialisasi rasial bapak dan ibudari semua subjek. Berdasarkan etnik, terdapat perbedaan yang bermaknadengan Melayu Malaysia menunjukkan skor paling tinggi yang menekankan kebanggaan rasial dan promosikecurigaan untuk anaknya. Dibahas implikasi dari hasil temuan ini.